Cuscuta species: Model organisms for haustorium development in stem holoparasitic plants - Jhu, Min-Yao; Sinha, Neelima R. (Frontiers in Plant Science, 2022)
Parasitic plants are notorious for causing serious agricultural losses in many countries. Specialized intrusive organs, haustoria, confer on parasitic plants the ability to acquire water and nutrients from their host plants. Investigating the mechanism involved in haustorium development not only reveals the fascinating mystery of how autotrophic plants evolved parasitism but also provides the foundation for developing more effective methods to control the agricultural damage caused by parasitic plants. Cuscuta species, also known as dodders, are one of the most well-known and widely spread stem holoparasitic plants. Although progress has been made recently in understanding the evolution and development of haustoria in root parasitic plants, more and more studies indicate that the behaviors between root and stem haustorium formation are distinct, and the mechanisms involved in the formation of these organs remain largely unknown. Unlike most endoparasites and root holoparasitic plants, which have high host-specificity and self- or kin-recognition to avoid forming haustoria on themselves or closely related species, auto-parasitism and hyper-parasitism are commonly observed among Cuscuta species. In this review, we summarize the current understanding of haustorium development in dodders and the unique characteristics of their parasitizing behaviors. We also outline the advantages of using Cuscuta species as model organisms for haustorium development in stem holoparasitic plants, the current unknown mysteries and limitations in the Cuscuta system, and potential future research directions to overcome these challenges.